Effect of subsurface drain spacing and nitrogen level on yield and growth of upland cotton (Gossypium hirsutum) and pearl millet (Permisetum glaucum) in saline soil - Singh, K N; Sharma, D P (The Indian Journal of Agricultural Sciences, 2012)
A field study was conducted during 1985—87 to study the effect of.3 drain spacing (25,50 and 75 m) and 3 levels of nitrogen (60,80 and 100 kg N/ha) for upland cotton (Gossypitum hirsutum L.) and 3 levels of N (80, 100 and 120 kg N/ha) for pearl millet [Pennisetum glaucum (L.) R. Br emend Stunt7] on soil salinity, growth and crop yield on a sandy-loam saline soil (Calclorthid) Monsoon rain and continuous cropping decreased the soil salinity considerably, but the decrease was more in drain spacing of 25 m than of 50 and 75 m, The increase in drain spacing significantly decreased the plant height, dry weight, number of bolls and seed-cotton yield/plant as well as seed-cotton yield during 1985. During 1986 and 1987 the drain spacing did not significantly affect plant characters and yields of both the crops, becouse the soil salinity decreased considerably in all the drain spacing during these years. The growth yield attributes and yield of cotton increased significantly with the application of 100 and 80 kg N/ha compared with 60 kg N/ha in all the years. In pearl millet the yield attributes and yields of grain and stover increased significantly with the application of J 20 kg N/ha compared with that of 100 and 80 kg N/ha. Thus cotton and pearl millet could be grown in saline soil under fiend conditions up to ECe7.5 and 6.5 dS/m (0-40 cm depth at sowing) respectively without affecting yield significantly.